Improving the efficiency of livestock farm wastewater treatment with combined anaerobic reactor and anaerobic filter technology - Sanphoti, Nirawan; Ruengruehan, Kaiwit (Edelweiss Applied Science and Technology, 2026)
Highly concentrated wastewater from local cattle farming requires treatment before being discharged into the environment. Anaerobic wastewater treatment is popularly employed, but the efficiency of removing high amounts of organic matter still has limitations. The objective of this study was to evaluate the efficiency of the combined anaerobic reactor. We investigated the effects of Chemical Oxygen Demand (COD) loading rate, hydraulic retention time (HRT), and greenhouse gas emissions. The volume of the total reactor is 1,050 liters. The retention times ranged from 0 to 28 hours, while COD loading rates were 0.39-1.17 kg-COD/m³-d. The results showed that the wastewater before treatment had a COD value of 2,253.5 ± 683.1 mg/L, Total Kjeldahl Nitrogen (TKN) 144.0 ± 31.5 mg/L, and Total Phosphorus (TP) 26.0 ± 5.5 mg/L. After treatment, the combined anaerobic reactor and anaerobic filter (AR/AF) system with 28 hours of retention time removed COD up to 68.15% and TKN up to 46.67%. The suitable COD loading rate was 0.39 kg-COD/m³-d, as the system eliminated COD up to 69.37% and TKN up to 39.47%. Compared to only AR, the AR/AF system was 79% more efficient and produced low greenhouse gas emissions, equivalent to 21.64 kg CO₂e per year.